A study on revisit intention and customer satisfaction towards service quality provided at AEON Bandaraya Melaka / Ruhaisha Ibrahim, Maizurah Abdul Razak and Mohamad Fariq Azrin Abd Rahman - Ibrahim, Ruhaisha; Abdul Razak, Maizurah; Abd Rahman, Mohamad Fariq Azrin (2014)
Nowadays, tourism is becoming an important industry in the world. Tourism is one of the most vibrant economic generators (Habibi, Abdul Rahim, Ramachandran, & Chin, 2008). According to World Tourism Organization (UNWTO, 2013), international tourist arrivals reached 1.035 billion in 2012 with 4% growth, that is an additional of 39 million tourists. A total of 145 countries and territories around the world monitored by UNWTO, including virtually all major destinations, have reported monthly or quarterly data on international tourists arrivals for 2013. UNWTO World Tourism Barometer estimated that international tourist arrivals grew with additional 52 million by 5% in 2013, which reaching a record 1,087 million